Endocrine-Disrupting Compounds in Urban Soils of Malaysia: Occurrence, Contamination, and Impacts on Health and the Environment - Lie, Michael; Kasongo, Joseph; Mtui, Elias; Rubiyatno; Tongco, Jovale Vincent (Tecno Scientifica Publishing, 2024)
Endocrine-disrupting compounds (EDCs) have garnered increasing concern in recent years due to their association with severe health issues and significant environmental impacts. EDCs, which can interfere with endogenous hormone systems, are diverse in structure and are often characterized by low molecular mass and halogen substitutions. Their presence in the environment, originating from both natural and synthetic sources, has been well-documented in water bodies, but studies on their occurrence in soils remain limited. This review provides a comprehensive overview of the occurrence, contamination, and impacts of EDCs in the urban soils of Malaysia. The paper discusses the primary sources of EDCs, including pharmaceuticals, pesticides, industrial chemicals, and combustion byproducts, and examines the pathways through which these compounds enter the soil. Health risks associated with exposure to EDCs, as well as their ecological consequences, are also explored. The review highlights the current status of EDCs contamination in Malaysian soils, identifies gaps in research, and outlines the challenges in monitoring and mitigating these contaminants. Understanding the dynamics of EDCs in soil is crucial for developing effective strategies to protect human health and the environment in urban settings.